The Using of Media in Learning Fiqh to the Islamic Education Department of Education and Teacher Faculty of IAIN Imam Bonjol Padang - Sabri, Ahmad; Gusmaneli, Gusmaneli; Gusmaneli, Gusmaneli (Institut Agama Islam Negeri Imam Bonjol Padang, 2015)
The using of media in learning is one of important aspects to be applied in learning process, the delivery of learning material is easy to understand, in addition to the provide more concrete learning, specially in the achievement of learning objectives. The aims of this study is to reveal the use of Media in Learning Fiqh in the Department of Islamic Education, Education and Teaching Faculty of IAIN Imam Bonjol Padang. This study used a qualitative descriptive method, the informants of this study is consisted of lecturers who teach jurisprudence at the Department of Islamic education, the other jurisprudence lecturers, students and subsequently increased in accordance with the purposes of the data obtained. Data collected by using observation, interviews, and documentation, to the validity of the data obtained, it is conducted the triangulation during the research process. The research results revealed that the Use of Media in Learning Fiqh of the Department of Islamic Education in Teaching Faculty of IAIN Imam Bonjol Padang by lecturers already in used, such as using a doll to organize the corpse, shroud, perfume, coffin corpse and occasional lecturer use media electronics such as laptop. This was due to the limited facilities and infrastructure that provide in Department of Islamic Education, Tarbiyah Faculty of IAIN Imam Bonjol Padang, and the instability of electricity power, thus, the most frequently media that is used by lecturer is a whiteboard using the discussion method.Â Keywords: Media, Learning of jurisprudence, DepartmentÂ of Islamic studiesCopyright Â© 2015 by Al-Talim All right reserved